Position of JMC Graduates: A Tracer Study - Sharma, Dvilal (Janapriya Journal of Interdisciplinary Studies, 2017)
The linkage between demand and supply of graduates instill a great significance in any study of higher education. The increasing trend of graduates may ultimately make the job market highly competitive. Due to high competition in job market there are high options for employer searching for new recruitment. To the best of study team, limited research has been carried out in higher education and none of the empirical studies have been found with regard to the absorption of the graduates in the job markets. Much of the studies discussed only challenges and policy intervention part. With this context, the status of graduates of JMC (a QAA Certified Institution) needs to be identified. It is widely believed that JMC has helped in building a nucleus of professionals in the related filed in Nepal and abroad. Though up-to-date information regarding the placement of JMC graduates is not available, it can be assumed that the graduates from JMC have been working in the various positions in the field of service, manufacturing, academia, and NGO/INGOs sectors in reputed and well established national and international organizations in the country and abroad. The main objective of this study is to trace out the students who have graduated from JMC as of 2009 to 2013 in various streams such as BBS, BBA, BA, B Sc and B Ed. The survey instrument was adapted from a questionnaire drafted by University Grants Commission Nepal, and it was slightly modified in its layout for the ease of handling. The questionnaire included both close-ended and opened questions. The expansion of higher education has increased the number of graduates entering into job market in Nepal and abroad. Graduates have felt easy to get enrollment in job market after attaining academic program in this campus. Graduates get insight in skills; attitude and knowledge for their job performance as well as improved work efficiency and communication skills after proceeding from this campus. Similarly the graduates have been able to improve their information technology skills and team spirit from the academic program offered by the campus. Janapriya Journal of Interdisciplinary Studies, Vol. III (December 2014), Page: 23-33